Technology in the Spanish Heritage Language Classroom: Can Computer-Assisted Language Learning Help? - Íñigo, Yanguas (Hispania, 2018)
Whereas myriad studies have been published in the field of Computer-Assisted Language Learning (CALL) in the past thirty years, research on the use and implementation of technology in the teaching and learning of Spanish as a heritage language (SHL) is very scarce. This study is aimed for those SHL instructors and researchers who are interested in incorporating technology and want to make an informed approach to the subject. Our goal is to provide the reader with the necessary background information in order to build a stronger SHL curriculum and point to some common tools that could be useful in that endeavor. Under the assumption that the SHL learner has a specific set of linguistic needs determined mainly by their socio-cultural upbringing, we contend that the teaching and learning of SHL in the United States should benefit from the advances made using technological tools in the L2 field. Furthermore, we argue that technology offers teachers and school administrators the opportunity to successfully cater to different students' needs in the SHL classroom. In addition, we discuss a variety of delivery methods and ideas that could be put into practice and offer further reading suggestions for instructors to examine in order to make an informed implementation of the technological tools available.